Fungal 7-epi-10-deacetyltaxol produced by an endophytic Pestalotiopsis microspora induces apoptosis in human hepatocellular carcinoma cell line (HepG2) - Kamalraj Subban; Satpal Singh; Ramesh Subramani; Muthumary Johnpaul; Jayabaskaran Chelliah (BMC, 2017)
Abstract Background Paclitaxel (taxol) is a potent anticancer drug that is used in the treatment of a wide variety of cancerous. In the present study, we identified a taxol derivative named 7-epi-10-deacetyltaxol (EDT) from the culture of an endophytic fungus Pestalotiopsis microspora isolated from the bark of Taxodium mucronatum. This study was carried out to investigate the effects of fungal EDT on cell proliferation, the induction of apoptosis and the molecular mechanisms of apoptosis in human hepatoma HepG2 cells in vitro. Methods The endophytic fungus was identified by traditional and molecular taxonomical characterization and the fungal EDT was purified using column chromatography and confirmed by various spectroscopic and chromatographic comparisons with authentic paclitaxel. We studied the in vitro effects of EDT on HepG2 cells for parameters such as cell cycle distribution, DNA fragmentation, reactive oxygen species (ROS) generation and nuclear morphology. Further, western blot analysis was used to evaluate Bcl-2-associated X protein (Bax), B-cell lymphoma 2 (Bcl-2), p38-mitogen activated protein kinase (MAPK) and poly [ADP-ribose] polymerase (PARP) expression. Results We demonstrate that the fungal EDT exhibited significant in vitro cytotoxicity in HepG2 cells. We investigated cytotoxicity mechanism of EDT in HepG2 cells. The results showed nuclear condensation and DNA fragmentation were observed in cells treated with fungal EDT. Besides, the fungal EDT arrested HepG2 cells at G2/M phase of cell cycle. Furthermore, fungal EDT induced apoptosis in HepG2 cells in a dose-dependent manner associated with ROS generation and increased Bax/Bcl-2 ratio, p38 MAPKs and PARP cleavage. Conclusions Our data show that EDT induced apoptotic cell death in HepG2 cells occurs through intrinsic pathway by generation of ROS mediated and activation of MAPK pathway. This is the first report for 7-epi-10-deacetyltaxol (EDT) isolated from a microbial source.